Investigating the Effect of Digital Technologies, Energy Consumption and Climate Change on Customer's Experience: A Study from Indonesia - Sasmoko, Sasmoko; Mihardjo, Leonardus W. Wasono; Alamsjah, Firdaus; Elidjen, Elidjen; Tarofder, Arun Kumar (International Journal of Energy Economics and Policy, 2019)
The objective of this study is to investigate the effect of digital transformation, energy consumption and Climate change on customer experience in the region of Indonesia. Research design is based on primary data collection through structural questionnaire. For customer experience, two factors under the title of hedonic and recognition are finalized. Digital transformation is observed through smart technologies. A sample of 282 respondents from Indonesian economy is selected and confirmatory factor analysis CFA is applied. All items of selected variables reflect reasonable factor loading, providing a good way for the regression analysis. Findings through regression indicates that awareness of smart technologies is increasing customer's experience in the form of entertaining, sense of comfort and educational. Learning of smart technologies has a significant influence on customer experience through entertaining and educational. Renewable energy consumption factor (usage of gas is friendly) has a significant and direct influence on all items of hedonic except sense of comfort. For recognition, all items are directly and significantly affected by the GFRIENDLY except sense of beauty. This study has significant covered the literature gap from the context of digital technologies, consumption of energy from new sources and climate change for better customer experience. Managerial implication of the study provides an evidence for the relevant experts in their field. Keywords: Digital transformation, energy consumption, climate change, factor analysis. JEL Classifications: N70, Q54 DOI: https://doi.org/10.32479/ijeep.8280